Penile length of newborns and children in Surakarta, Indonesia - Annang Giri Moelyo; Melita Widyastuti (Paediatrica Indonesiana, 2013)
Background Penile length is a factor for assessing abnormalities inexternal genitalia. To diagnose micropenis, a condition in whichpenile length is < - 2.5 standard deviations (SD), a reference isrequired for diagnosis. Age and race/ethnic groups are factorsthat contribute to normal penile length. To date, Indon esia doesnot have such a reference for normal penile length in newbornsand children.Objective To assess normal penile length in newborns and childrenin Surakarta, Central Java, in which the majority population isofJavanese ethnicity.Methods We studied male newborns and children who werepatients in Moewardi Hospital from January 2011 to January2012. We included males aged 0-18 years whose parents providedinformed consent. We excluded children with undescendedtestis, hypospadia, ambiguous genitalia, con genital anomalies,or syndromes (such as Down syndrome). For penile len gthmeasurements, we stretched the flaccid penis, depressed thepubic fat and placed a wooden spatula vertically along the dorsalpenis. The penile length was measured from the penile baseto the tip of the glans excluding the prepuce. Measurementswere performed three times and a mean value was calculatedfor each subject.Results Of the 300 subjects, 100 were newborns and 200 werechildren aged 1 month - 18 years. Two hundred ninety-six subjects(98.7%) were Javanese. The mean penile lengths of preterm(gestational age 30-36 weeks) and term (gestational age > 36weeks) newborns were 1.88 (SD 0.14) cm and 2.3 7 (SD 0.26) cm,respectively. The mean penile lengths by age groupings were asfollows: 0-<6 months, 2.67 (SD 0.58) cm; 6- < 12 months, 2.67(SD 0.58) cm; 1- <3 years, 2.80 (SD 0.84) cm; 3-<5 years, 3 .50(SD 0.55) cm; 5- <7 years, 3 .50 (SD 0.71) cm; 7-<9 years, 3 .85(SD 0.53 ) cm; 9-<ll years, 4.50 (SD 0.71) cm; 11-< 13 years,4.63 (SD 1.13) cm; 13-< 15 years, 5.53 (SD 1.45) cm; and 15-18years, 6.16 (SD 1.19) cm.Conclusion Normal penile length in boys in Surakarta is smallerthan the normal range reference currently in use.